2022
DOI: 10.3390/cancers14174175
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Safety and Effectiveness of Robotic-Assisted Surgery in Patients with Rectal Cancer: Real-World Experience over 8 Years of Multiple Institutions with High-Volume Robotic-Assisted Surgery

Abstract: The perioperative and short-term oncological outcomes of robotic-assisted rectal surgery (RRS) are unclear. This retrospective observational study enrolled patients with rectal adenocarcinoma undergoing RRS from three high-volume institutions in Taiwan. Of the 605 enrolled patients, 301 (49.75%), 176 (29.09%), and 116 (19.17%) had lower, middle, and upper rectal cancers, respectively. Low anterior resection (377, 62.31%) was the most frequent surgical procedure. Intraoperative blood transfusion was performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Although none of the differences were significant, robot‐assisted surgery tended to show a longer hospital stay than laparoscopic surgery, possibly due to the lower percentage of educational hospitals used for robot‐assisted surgery (46.5% vs. 53.5%). Huang et al 27 reported on the postoperative results of robot‐assisted surgery for rectal cancer at three high‐volume centers in Taiwan. The complication rate was 14.4%, which was lower than previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Although none of the differences were significant, robot‐assisted surgery tended to show a longer hospital stay than laparoscopic surgery, possibly due to the lower percentage of educational hospitals used for robot‐assisted surgery (46.5% vs. 53.5%). Huang et al 27 reported on the postoperative results of robot‐assisted surgery for rectal cancer at three high‐volume centers in Taiwan. The complication rate was 14.4%, which was lower than previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, they reported a significantly lower distant recurrence rate in the robotic arm for patients with T3/T4 tumors (44.8% vs. 9.8), arguing a potential benefit of robotic resections for this subset of patients [52]. Huang et al, in multi-institutional retrospective work, documented a 5-year overall and disease-free survival of 91.1% and 86.3% for 605 patients with stages I-III rectal cancer who underwent robotic TME [53].…”
Section: Robotic Surgery: Long-term Oncological Outcomesmentioning
confidence: 99%
“…[7] However, the prognosis was not significantly improved in patients with ultralow rectal cancer compared to patients with middle and upper rectal cancers. [8] Abdominoperineal combined resection was once a surgical procedure for the treatment of ultralow rectal cancer, but it seriously affects the quality of life of patients. [9] With the development of preoperative neoadjuvant radiotherapy and chemotherapy, the technology of laparoscopic surgery continues to improve, and with the evolution of surgical instruments, [10] the success rate of sphincter-sparing surgery (SSS) for ultralow rectal cancer has increased.…”
Section: This Study Was Funded By the Guangxi Science And Technology ...mentioning
confidence: 99%
“…[7] However, the prognosis was not significantly improved in patients with ultralow rectal cancer compared to patients with middle and upper rectal cancers. [8]…”
Section: Introductionmentioning
confidence: 99%